2015
DOI: 10.3109/13880209.2015.1033560
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofHeliopsis longipesethanolic extract on mouse spermatozoain vitro

Abstract: Context: Heliopsis longipes (A. Gray) Blake (Asteraceae), a plant native to Mexico, is used in traditional medicine as analgesic and microbicide. The main component in the H. longipes ethanolic extract (HLEE) is affinin, as determined by HPLC/UV-visible and NMR measurement. To date, there is no documented evidence on the spermicidal activity of this extract. Objective: The objective of this study was to assess in vitro the effectiveness of HLEE as spermicide. Materials and methods:The spermicidal activity of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Our results indicated that affinin is able to activate the NO/cGMP, CO/cGMP, H 2 S/KATP, and PGI2/cAMP signaling pathways, and considering that the triggering of these four signaling pathways depends on the activation of molecular targets located on the endothelium layer, it is very likely that this alkamide might be acting on molecular targets, whose activation leads to an increase in Ca 2+ levels in the endothelial cells. The chemical structure of N -alkylamides or alkamides [ 63 ], like affinin [ 13 , 64 , 65 ] resembles that of fatty acid amides [ 66 , 67 , 68 , 69 ], and the endogenous cannabinoid N -arachidonylethanolamine or anandamide [ 70 ]. This molecule produces a potent vasodilator effect through several proposed mechanisms that include activation of TRPV1 channels and G-coupled receptors, such as CB 1 , CB 2 , and endothelial non-CB 1 /non-CB 2 [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that affinin is able to activate the NO/cGMP, CO/cGMP, H 2 S/KATP, and PGI2/cAMP signaling pathways, and considering that the triggering of these four signaling pathways depends on the activation of molecular targets located on the endothelium layer, it is very likely that this alkamide might be acting on molecular targets, whose activation leads to an increase in Ca 2+ levels in the endothelial cells. The chemical structure of N -alkylamides or alkamides [ 63 ], like affinin [ 13 , 64 , 65 ] resembles that of fatty acid amides [ 66 , 67 , 68 , 69 ], and the endogenous cannabinoid N -arachidonylethanolamine or anandamide [ 70 ]. This molecule produces a potent vasodilator effect through several proposed mechanisms that include activation of TRPV1 channels and G-coupled receptors, such as CB 1 , CB 2 , and endothelial non-CB 1 /non-CB 2 [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…15240-062, NY, USA). We used 1 µL of dimethylsulfoxide (DMSO) for each 2 µg of sample for the dilution and treatment preparations for HLEE and affinin [8,83,84]. Experiments were performed using BSCM + DMSO for the negative control; BSCM + 30 ng/mL basic fibroblast growth factor (FGF-b) (Peprotech, Cat.…”
Section: Pharmacological Assays 451 Rat Aortic Ring Assaymentioning
confidence: 99%